Half the Battle : Civilian Morale in Britain During the Second World War - Mackay, Robert (Manchester University Press, 2003)
How well did civilian morale stand up to the pressure of total war and what factors were important to it? Rejecting contentions that morale fell short of the favourable picture presented during World War II and since, this work shows how government policies for maintaining morale were put in place.